Advances of psychiatric disturbances of cancer patients at the end of life - de Walden-Gałuszko, Krystyna (Przewodnik Lekarza/Guide for GPs, 2009)
There are two groups of psychiatric disturbances in these cancer patients – adjustment disorders and neuropsychiatric disturbances. The first group consists mainly of anxiety and depressive syndromes. The drugs should be appropriate for the specific symptoms. In general anxiety disorder we started with anxiolytic benzodiazepines (BDP) and after 14 days continued the treatment with other anxiolytics (e.g. buspirone, doxepin). Panic disorder in the first step BDP and propranolol, second step (as prophylaxis) selective serotonine reuptake inhibitors (SSRI). Depressive hypoactive syndrome should be treated with psychoactive antidepressants (e.g. SSRI or venlafaxine). Hyperactive depression reacts better to sedative antidepressive drugs: e.g. mianserin, mirtazapine, trazodone. In mixed syndromes we use moclobemide, tianeptine or venlafaxine (with BDP) at the beginning. Delirium is a typical example of a neuropsychiatric disturbance. We treat mainly hyperactive delirium. In the acute stage of delirium we use antipsychotics (haloperidol, olanzapine, risperidone, quetiapine). Older patients with Parkinson’s disease should be treated with small doses of risperidone. Neuroleptics should be completed with anxiolytics (midazolam, lorazepam). In the case of lack of therapeutic effect the neuroleptics should be replaced with clorazepate dipotassium (i.m. or i.v. ). Hypoactive form of delirium usually appears in the last days of life and we provide then only by typical somatic symptom control (e.g. pain).